Controlled graphite surface functionalization using contact and remote photocatalytic oxidation. (February 2021) - Ostyn, Niels R.; Thijs, Barbara; Steele, Julian A.; Sree, Sreeprasanth Pulinthanathu; Wangermez, Wauter; Teyssandier, Joan; Minjauw, Matthias M.; Li, Jin; Detavernier, Christophe; Roeffaers, Maarten B.J.; De Feyter, Steven; Martens, Johan A.
Abstract: Controlled chemical functionalization of graphite's outer surface layers into photocatalytically oxidized graphite (POG) is reported. POG can be easily prepared via a UV-driven process using titanium dioxide photocatalyst in molecular oxygen and water vapor at relatively low temperature. The photo-oxidation offers a mild and highly controllable process, providing a chemically tailored POG surface with moderate oxidation degree. Raman spectroscopy is used to directly track the transformation of planar sp 2 -hybridized carbon to oxygenated sp 3 -hybridized chemical functions. Covalent carbon-oxygen bonding at the graphite surface upon oxidation is confirmed by XPS. This vapor-phase process in absence of hazardous liquid chemicals causes oxygen-functionalized and thermally stable POG with an oxygen content up to 14 wt%, suggesting it to be useful for electrocatalysis. Oxidation can be performed with the photocatalyst in direct contact with graphite or mounted at a distance (remote mode). This titanium dioxide-based photocatalytic oxidation is also effective on refractory highly oriented pyrolytic graphite (HOPG). HRSEM and AFM reveal the existence of differently sized surface blisters on natural graphite and HOPG following oxidation. Addition of nitric oxide to the gas mixture accelerates the photoreaction and promptly leads to graphite surface pits and edge erosion due to excessive oxidative strength. Graphical abstract: Image 1 Highlights: Graphite surface functionalization caused by mild photocatalytic oxidation. sp 2 -hybridized carbon partially converted into sp 3 carbon following photo-oxidation. Tunable graphite surface oxidation enabled by controlled vapor-phase process. Graphite oxidation performed by contact and remote titanium dioxide photocatalysis. Stable photocatalytically oxidized graphite (POG) with moderate oxygen content.